Pneumatic Vitreolysis using C3F8 Gas in Treatment Naive Patients with Vitreomacular Traction - Marková, Kateřina; Němec, Pavel; Červený, Petr; Havlik, Jan; Rejmont, Leoš; Tesař, Jan; Morin, Hana; Šín, Martin (Ceska a slovenska oftalmologie, 2024)
PURPOSE: Evaluation of the effectiveness of pneumatic vitreolysis in disrupting vitreomacular traction in our own cohort of patients. METHODOLOGY: Prospective follow-up of 21 eyes of 18 patients with focal VMT (adhesion width < 1500 µm) who underwent intravitreal injection of 0.3 ml of 100% perfluoropropane between January 2015 and December 2020. The patients were observed for 90 days. RESULTS: Release of VMT was achieved on the 28th day of observation in 15 out of 21 eyes (71.4%), and by the 90th day in 19 out of 21 eyes (90.5%). The average width of adhesion in our patients was 382 µm (±212 µm). Average best corrected visual acuity in our cohort was initially 0.77 (±0.21), after 28 days 0.74 (±0.30), and after 3 months 0.82 (±0.21). At the end of the follow-up period, we did not observe a statistically significant improvement in vision. Macular holes developed in two eyes, but spontaneously closed within 1 month of observation, and no more complications were observed in the cohort. CONCLUSION: Pneumatic vitreolysis by intravitreal injection of C3F8 gas is an effective and inexpensive option for the management of symptomatic vitreomacular traction. The incidence of serious adverse events in our follow-up was significantly lower than in recently published series. The method of management should be selected individually according to the parameters of adhesion, macular hole and associated ocular pathologies.
Keywords: sklivec; Fluorocarbons; Male; zraková ostrost; C3F8; následné studie; perfluorocarbons; injekce intravitreální; odchlípení sklivce; prospective study; Aged; Prospective Studies; mužské pohlaví; senioři; nemoci retiny; Vitreous Body; Visual Acuity; Follow-Up Studies; senioři nad 80 let; lidé; vitrectomy; ženské pohlaví; Humans; Intravitreal Injections; fluorokarbony; Pars plana vitrectomy; Aged, 80 and over; vitreous detachment; intravitreal injection; Retinal Diseases; Female; Vitreous Detachment; lidé středního věku; Middle Aged; prospektivní studie